American Cancer Society nutrition and physical activity guideline for cancer survivors. (16th March 2022) - Rock, Cheryl L.; Thomson, Cynthia A.; Sullivan, Kristen R.; Howe, Carol L.; Kushi, Lawrence H.; Caan, Bette J.; Neuhouser, Marian L.; Bandera, Elisa V.; Wang, Ying; Robien, Kimberly; Basen‐Engquist, Karen M.; Brown, Justin C.; et al.
Abstract: The overall 5‐year relative survival rate for all cancers combined is now 68%, and there are over 16.9 million survivors in the United States. Evidence from laboratory and observational studies suggests that factors such as diet, physical activity, and obesity may affect risk for recurrence and overall survival after a cancer diagnosis. The purpose of this American Cancer Society guideline is to provide evidence‐based, cancer‐specific recommendations for anthropometric parameters, physical activity, diet, and alcohol intake for reducing recurrence and cancer‐specific and overall mortality. The audiences for this guideline are health care providers caring for cancer survivors as well as cancer survivors and their families. The guideline is intended to serve as a resource for informing American Cancer Society programs, health policy, and the media. Sources of evidence that form the basis of this guideline are systematic literature reviews, meta‐analyses, pooled analyses of cohort studies, and large randomized clinical trials published since 2012. Recommendations for nutrition and physical activity during cancer treatment, informed by current practice, large cancer care organizations, and reviews of other expert bodies, are also presented. To provide additional context for the guidelines, the authors also include information on the relationship between health‐related behaviors and comorbidities, long‐term sequelae and patient‐reported outcomes, and health disparities, with attention to enabling survivors' ability to adhere to recommendations. Approaches to meet survivors' needs are addressed as well as clinical care coordination and resources for nutrition and physical activity counseling after a cancer diagnosis.